Estratégias do tempo e discurso narrativo: relações entre história e psicanálise em Michel de Certeau - Robson Freitas de Miranda Junior (2017)
The aim of this research is to analyze the ways in which the french historian Michel de Certeau appropriated psychoanalysis in his reflections on history. Firstly, we present some important readings that have been made of the work of this historian, by author such as Luce Giard, Paul Ricoeur, François Dosse, Roger Chartier e François Hartog. Form these authors, we will try to situate our own perspective of Certeau's work, evidencing the importance of psychoanlysis in it. Next, we will discuss the certeaunian notion of "historiographic operation", emphasizing that the author understood history as a heterology, that is, a kind of logos of otherness. From this conception, we will delineate the specificities of Certeau's appropriations of psychoanalytic theory, specially, to conceive the concept of "historical fiction", to propose other strategies of temporality for history, as well as to learn a new theory of historical narrativity with Freud.